Estimating human health risks associated with heavy metal exposure from bottled water using Monte Carlo simulation - Nezam Mirzaei; Safa Kalteh; Hakime Zamani-Badi; Heshmatallah Moradpour; Zeinab Parmoozeh; Mansour Baziar (Heliyon, 2023)
Water is the most important non-organic compound for living cells, and the life of all living organisms depends on it. Water is not found purely in nature, but it always contains some solutes, suspended matters and soluble gases. In this study, 11 bottled water brands (500 mL) were sampled across the Kashan city market to determine the concentration of selected heavy metals (Cr, Cd, Pb, Ni and As) and evaluated their potential risks following consumption. The concentration range of Cr, Cd, Pb, Ni and As were 5–34 μg/L, 1.5–7 μg/L, 1–7 μg/L, 2–29 μg/L, <LOD – 3.5 μg/L, respectively. The heavy metals (HMs) concentration in this study was compared with other national and international studies on bottled water and other drinking water sources. Additionally, the results of non-carcinogenic health risk assessments using point estimations and Monte Carlo Simulations (MCS) showed that the concentration of HMs in none of the samples pose adverse health effects. However, it was found that drinking the studied bottled water may potentially lead to carcinogenicity over the lifetime. Lack of including spring water and larger-sized (1.5 L) bottled water samples, though less consumed than the samples of this study and lack of study on children's exposure level can be mentioned as potential limitations.